Childhood systemic lupus erythematosus in Latin America. The GLADEL experience in 230 children (2008)
ABSTRACT: To evaluate disease characteristics of childhood onset SLE in Latin America and to compare this information with an adult population in the same cohort of GLADEL. A protocol was designed as a multicenter, multinational, inception cohort of lupus patients to evaluate demographic, clinical, laboratory and serological variables, as well as classification criteria, disease activity, organ damage and mortality. Descriptive statistics, chi square, Fisher´s exact test, Student´s t test and multiple logistic regression were used to compare childhood and adult onset SLE. 230 patients were < 18 years and 884 were adult SLE patients.Malar rash, fever, oral ulcers, thrombocytopenia and hemolytic anemia and some neurologic manifestations were more prevalent in children (p < 0.05). On the other hand, myalgias, Sjögren’s syndrome and cranial nerve involvement weremore frequently seen in adults (p < 0.05). Afro-Latin-American children had a higher prevalence of fever, thrombocytopenia and hemolytic anemia. White and mestizo children had a higher prevalence of malar rash. Mestizo children had a higher prevalence of cerebrovascular disease and cranial nerve involvement. Children met SLE ACR criteria earlier with higher mean values than adults (p: 0.001). They also had higher disease activity scores (p: 0.01), whereas adults had greater disease damage (p: 0.02). In Latin America, childhood onset SLE seems to be a more severe disease than adults. Some differences can be detected among ethnic groups. Lupus (2008) 17, 596–60